Racial and ethnic differences in comorbid psychosis: a population-based study - Sankoh, Mariam; Clifford, James; Peterson, Roseann E.; Prom-Wormley, Elizabeth (Frontiers in Psychiatry, 2024)
Differences in the prevalence of psychiatric conditions such as psychosis as well as patterns of comorbidity for psychosis have been reported between racial and ethnic groups. It is unclear whether those differences are consistent for comorbid psychosis. METHODS. Selfreported diagnostic data from American adults ages 18-99 participating in the Collaborative Psychiatric Epidemiology Surveys (CPES) (N ~ 11,844) were used to test the association between four racial and ethnic group categories (White, Asian, Hispanic, Black) and comorbid psychosis. Comorbid psychosis was measured as a 4-level categorical variable (No mental illness nor psychosis, Mental Illness, Psychosis only, comorbid psychosis (i.e., Psychosis + Mental Illness). Chi-square tests were used to determine significant differences in the prevalence of comorbid psychosis by race and ethnicity. A multinomial logistic regression was used to test the association between racial and ethnic classifications and comorbid psychosis after adjusting for common demographic characteristics (i.e., education, sex, income, and age). RESULTS. Relative to White participants, Hispanic and Asian participants were less likely to be affected with comorbid psychosis. (Adjusted Odds Ratio, AORAsian = 0.32, CI = 0.22 -0.47, p <0.0001, AORHispanic = 0.66, CI = 0.48 -0.92, p = 0.012). Relative to White participants there was not significant association for comorbid psychosis in Black participants (AORBlack = 0.91, CI = 0.70 -1.20, p = 0.52) In contrast Hispanic and Black participants were more likely to report psychosis alone (AORHispanic = 1.94, CI = 1.27-2.98, p = 0.002, AORBlack = 1.86, 1.24-2.82, p = 0.003) compared to White participants. CONCLUSION. There were different patterns of associations by race and ethnicity for psychosis and comorbid psychosis. The lower prevalence of comorbid psychosis in non-White groups may be due to underdiagnosis or underreporting of other mental disorders.